Multisystem Langerhans cell histiocytosis with primary cutaneous lesions. - Khaliulin, Y.G.; Filimonov, P.N.; Amelin, M.; Bizunova, M.; Raginskaya, O.; Tulupov, A.; Sergeeva, I.G. (European Journal of Pediatric Dermatology, 2015)
We report an additional case of pediatric multisystem Langerhans cell histiocytosis (LCH) with primary cutaneous lesions. A boy was born to a mother who had cytomegalovirus (CMV) infection during her pregnancy. During the first 1-3 months the patient had an acute CMV infection with involvement of skin, intestine, and liver. In the subsequent months the child had other cutaneous lesions diagnosed as molluscum contagiosum and chickenpox at the age respectively of 5 and 18 months; these lesions regressed in 6-8 weeks. When aged 25 months, the child had multiple exudative cutaneous lesions, hemorrhagic nail changes, gingival and lung lesions. These findings and the result of a cutaneous scalp biopsy led to the final diagnosis of multisystem Langerhans cell histiocytosis.